Quantitative validation of ICESat-2 ATL24 in shallow marine environments using reference-grade bathymetric data - Giribabu Dandabathula; Omkar Shashikant Ghatage; Subham Roy; Shweta Yadav; Apurba Kumar Bera; Sushil Kumar Srivastav (Marine Geodesy, 2026)

Importance of the inflammasome in gut-brain axis: from pathological driver to therapeutic target - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Inflammopharmacology, 2026)

Exosomes-mediated intercellular communication and their theragnostic potential against cancer and related disorders: a comprehensive review - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Biotechnology Letters, 2026)

Structural insights into TNF-α inhibition by bioactive compounds found in plants of North East India: in vitro validation and in silico investigations using QSAR, molecular docking, and dynamics simulations - Sarbani Dey Ray; Supratim Ray; Bibhas Pandit; Subham Ghosh; Anjali Murmu; Partha Pratim Roy; Jagadish Singh (Molecular Diversity, 2026)

Spermidine Attenuates Neuroimmune Dysfunction in Gulf War Illness via Modulation of the Gut- Brain Axis - Ayushi Trivedi; Subhajit Roy; Madhura More; Dipro Bose; Punnag Saha; Ram Kumar; Subham Sarkar; Jonathan Skupsky; Ashok Tuteja; Kimberly Sullivan; Nancy Klimas; Saurabh Chatterjee (Molecular Neurobiology, 2026)
Gulf War illness (GWI) affects nearly one-third of US veterans deployed during the 1990–1991 Gulf War (GW) and is characterized by chronic fatigue, neuroinflammation, and gut dysbiosis. Through comprehensive fecal metabolomics sequencing, our lab previously reported the depletion of beneficial metabolites including spermidine in the preclinical GWI mouse model. Spermidine is an endogenously synthesized polyamine known for its anti-inflammatory and mucosal barrier protective effects in various pathological diseases. Given its established role in mitigating intestinal inflammation and maintaining homeostasis, this study investigated the therapeutic potential of spermidine in a persistent (22 weeks) GWI mouse model, with a specific focus on gut–brain axis regulation. Our results demonstrated that spermidine effectively restored both microbial richness and diversity by selectively enriching beneficial bacterial taxa and suppressing growth of opportunistic pathogens, which are otherwise dysregulated following exposure to GW chemicals. Spermidine treatment also improved gut epithelial barrier integrity and reduced epithelial release of high-mobility group box 1 (HMGB1) into systemic circulation. Recent studies on GWI have implicated a critical role of gut-derived damage-associated molecular patterns (DAMPs), particularly HMGB1 in mediating neuroinflammation. Our findings indicate that systemic levels of HMGB1 critically influence the extent of blood–brain barrier (BBB) disruption and subsequent microglial activation. Mechanistically, spermidine activated intestinal aryl hydrocarbon receptor (AhR)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling, which played a role in limiting intestinal HMGB1 release and suppressing downstream receptor for advanced glycation end-product (RAGE)–mediated microglial activation in the brain. In vitro results indicate spermidine promoted AhR/Nrf2 nuclear translocation which reduced LPS-induced HMGB1 release from primary intestinal epithelial cells (IECs), effects abrogated by AhR inhibition. Additionally, we observed that HMGB1 directly induces microglial activation via RAGE receptors in immortalized microglial (IMG) cell lines in a dose-dependent manner. These results demonstrate that spermidine decreases neuroinflammation by modulating gut–brain axis pathophysiology associated with GWI. Together, this study demonstrates the therapeutic role of spermidine in ameliorating systemic and neurological disturbances in GWI. Graphical Abstract

Arbuscular mycorrhiza symbiosis—from molecular dialogues to biotechnological applications - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Mycological Progress, 2025)

Upcycling edible Musa balbisiana bracts waste into sustainable and possible 3D printable biomaterials - Shivam Rajput; Dipjyoti Sharma; Koushik Nandan Dutta; Subhadeep Roy; Subham Banerjee (Innovative Food Science & Emerging Technologies, 2025)

Determination of dust storm height using weak beam photons from ICESat-2 and relating with vertical wind profile - Giribabu Dandabathula; Subham Roy; Omkar Ghatage; Apurba Kumar Bera; Sushil Kumar Srivastav (Atmospheric Environment, 2025)

Mensuration of FABDEM’s vertical accuracy using ICESat-2 photon profiles over sloped terrains - Subham Roy; Omkar Ghatage; Giribabu Dandabathula (Spatial Information Research, 2025)

Formation, triggering, and motion factors for the snow avalanche on 30 June 2024 at the Kedarnath South Face in the Indian Himalayas - Giribabu Dandabathula; Subham Roy; Shabana Syal; Sahibnoor Kaur; Shwetambari Satpute; Satyanarayana Pondari; Apurba Kumar Bera; Sushil Kumar Srivastav (Landslides, 2025)

Brighter Nights, safer cities? Exploring spatial link between VIIRS nightlight and urban crime risk - Subham Roy; Indrajit Roy Chowdhury (Remote Sensing Applications: Society and Environment, 2025)

Intoxication in the city: Investigating spatial patterns and determinants of drugs and alcohol-related illegal activities in India's geostrategic corridor - Subham Roy; Indrajit Roy Chowdhury (Applied Geography, 2024)

Performance validation of High Mountain Asia 8-meter Digital Elevation Model using ICESat-2 geolocated photons - Giribabu Dandabathula; Subham Roy; Omkar Shashikant Ghatage; Vaibhav Balaso Kolase; Shwetambari Satpute; Koushik Ghosh; Sahibnoor Kaur; Satyanarayana Pondari; Apurba Kumar Bera; Sushil Kumar Srivastav (Journal of Mountain Science, 2024)

The rich-poor divide: Unravelling the spatial complexities and determinants of wealth inequality in India - Subham Roy; Suranjan Majumder; Arghadeep Bose; Indrajit Roy Chowdhury (Applied Geography, 2024)

On the factors controlling the incorporation of aluminium within titanites: a case study from medium pressure calc-silicate granulites in parts of the East Indian shield - Sirina Roy Choudhury; Anindita Dey; Subham Mukherjee; Sanjoy Sanyal; Subrata Karmakar; Pulak Sengupta (Mineralogy and Petrology, 2023)

Plant growth-promoting traits and activation of defense enzymes in traditional rice variety by fungal endophytes isolated from seeds of indigenous rice cultivars of Northeast India - Subham Roy; Anindita Sarma; Sushmita Paul; Dhurva Kumar Jha; Kumananda Tayung (South African Journal of Botany, 2023)

Multiscale GIS based-model to assess urban social vulnerability and associated risk: Evidence from 146 urban centers of Eastern India - Suranjan Majumder; Subham Roy; Arghadeep Bose; Indrajit Roy Chowdhury (Sustainable Cities and Society, 2023)

Nanoremediation strategies to address environmental problems - Muzamil Ahmad Rather; Shuvam Bhuyan; Ratan Chowdhury; Rahul Sarma; Subham Roy; Panchi Rani Neog (Science of The Total Environment, 2023)

Multi-influencing factor (MIF) and RS–GIS-based determination of agriculture site suitability for achieving sustainable development of Sub-Himalayan region, India - Subham Roy; Nimai Singha; Arghadeep Bose; Debanjan Basak; Indrajit Roy Chowdhury (Environment, Development and Sustainability, 2023)

Towards sustainable society: the sustainable livelihood security (SLS) approach for prioritizing development and understanding sustainability: an insight from West Bengal, India - Subham Roy; Arghadeep Bose; Debanjan Basak; Indrajit Roy Chowdhury (Environment, Development and Sustainability, 2023)

Formation of aluminous clinopyroxene-ilmenite-spinel symplectic assemblage in a regionally metamorphosed calc-silicate granulite from the Chotanagpur Granite Gneiss Complex, East Indian shield - Sirina Roy Choudhury; Anindita Dey; Subham Mukherjee; Sukanya Sengupta; Sanjoy Sanyal; Subrata Karmakar; Pulak Sengupta (Lithos, 2023)

Citizens’ perception towards landfill exposure and its associated health effects: a PLS-SEM based modeling approach - Subham Roy; Debanjan Basak; Arghadeep Bose; Indrajit Roy Chowdhury (Environmental Monitoring and Assessment, 2023)

Modeling and mapping geospatial distribution of groundwater potential zones in Darjeeling Himalayan region of India using analytical hierarchy process and GIS technique - Subham Roy; Arghadeep Bose; Goutam Mandal (Modeling Earth Systems and Environment, 2022)

Flood risk assessment using geospatial data and multi-criteria decision approach: a study from historically active flood-prone region of Himalayan foothill, India - Subham Roy; Arghadeep Bose; Indrajit Roy Chowdhury (Arabian Journal of Geosciences, 2021)

Reduction in concentration of PM2.5 in India’s top most polluted cities: with special reference to post-lockdown period - Subham Roy; Nimai Singha (Air Quality, Atmosphere & Health, 2021)